The effectiveness of media on distance learning based on Merrill's Taxonomy and CASR 147 - Moch Rifai; Novita Vindri Harini (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
According to Merrill, there are two dimensions of learning objectives: content and performance. For learning to achieve its goals, suitable media is needed. Moreover, the Covid-19 pandemic situation since 2019 requires learning to be distanced. Teachers and students must work together to achieve learning objectives. Several media can support learning, including text formats, audio/video tutorials, interactive multimedia, and simulator software. Especially for Aviation Vocational education which has a learning level guide at CASR 147, further analysis is needed on how these media can effectively achieve learning objectives. So, this study aims to analyze the effectiveness of media in distance learning based on Merrill's Taxonomy and CASR 147. Quantitative research methods are used with data from questionnaires and several interviews for data triangulation needs. Based on its effectiveness, the following are suggestions of learning media that can be used: audio/video tutorials, simulators, interactive multimedia, and text formats. Furthermore, it is necessary to conduct research that discusses media preferences based on students' learning styles to know the reasons for the results of media selection by students through questionnaires.